Anaemia in early childhood among Aboriginal and Torres Strait Islander children of Far North Queensland: a retrospective cohort study - Dympna Leonard; Petra Buttner; Fintan Thompson; Maria Makrides; Robyn McDermott (Elsevier, 2019)
Abstract Objective: Early childhood anaemia affects health and neurodevelopment. This study describes anaemia among Aboriginal and Torres Strait Islander children of Far North Queensland. Methods: This retrospective cohort study used health information for children born between 2006 and 2010 and their mothers. We describe the incidence of early childhood anaemia and compare characteristics of children and mothers where the child had anaemia with characteristics of children and mothers where the child did not have anaemia using bivariate and multivariable analysis, by complete case (CC) and with multiple imputed (MI) data. Results: Among these (n=708) Aboriginal and Torres Strait Islander children of Far North Queensland, 61.3% (95%CI 57.7%, 64.9%) became anaemic between the ages of six and 23 months. Multivariable analysis showed a lower incidence of anaemia among girls (CC/MI p<0.001) and among children of Torres Strait Islander mothers or both Aboriginal and Torres Strait Islander mothers (CC/MI p<0.001) compared to children of Aboriginal mothers. A higher incidence of anaemia was seen among children of mothers with parity three or more (CC/MI p<0.001); children born by caesarean section (CC/MI p<0.001); and children with rapid early growth (CC/MI p<0.001). Conclusion: Early childhood anaemia is common among Aboriginal and Torres Strait Islander children of Far North Queensland. Poor nutrition, particularly iron deficiency, and frequent infections are likely causes. Implications for public health: Prevention of early childhood anaemia in 'Close the Gap' initiatives would benefit the Aboriginal and Torres Strait Islander children of Far North Queensland - and elsewhere in northern Australia.